Analisis Adopsi Pemanfaatan Teknologi Digital Pada Usaha Mikro Kecil Menggunakan Framework TOE - Sari, Riska Rahma; Aryani, Reni; Arsa, Daniel (LPPM Universitas Dinamika Bangsa, 2025)
The advancement of digital technology has a great influence on the development of Micro and Small Enterprises (MSEs). However, the level of digital technology adoption by MSE actors is still relatively low. This study aims to analyze the factors that influence the adoption of digital technology using the Technology-Organization-Environment (TOE) framework. A quantitative approach was used with the Partial Least Square Structural Equation Modeling (PLS-SEM) method through SmartPLS 4.0. The research sample consisted of 97 MSEs in Jambi City engaged in the food and beverage sector. The questionnaire instrument was prepared based on the three dimensions of TOE: Technology, Organization, and Environment. The results showed that technological and environmental factors had a significant effect on the adoption of digital technology, while organizational factors did not show a significant effect. This may be due to the simple and informal organizational structure of MSEs. This finding shows that the TOE framework is relevant in analyzing the adoption of digital technology in MSEs and provides implications for business actors and policy makers to further emphasize technological and environmental aspects in the digitalization strategy of MSEs.